THE STUDENTS PERCEPTION OF LANGUAGE POLITENESS – BASED TEACHING MATERIALS IN SPEAKING SKILLS AT GERMAN LANGUAGE DEPARTMENT PATTIMURA UNIVERSITY AMBON - marantika, Juliaans; Lestuny, Carolina; Wenno, Eldaa C (Pattimura Excellence Journal of Language and Culture, 2021)
This research is aimed to obtain information about students' perceptions of politeness-based speaking skills teaching materials. The developed teaching materials were tried out in German Language Department, Pattimura University. The data was collected using a questionnaire technique to explore students' perspectives on teaching materials, while data analysis related to student perceptions was carried out using descriptive-analytic methods. The results showed that the theme chosen is a daily theme according to the daily communication needs of the beginner students, such as apologizing, asking, giving feedback or answering questions, giving suggestions, expressing opinions, etc. The teaching materials developed are also in accordance with the age level and students' language skills. Most of the students with language teaching materials that focus on (speaking skills) help them understand German language material easily. The form of training carried out by contrasting polite and unpolished utterances greatly helps students to distinguish appropriate speech according to politeness and will be able to use these speeches in daily communication. In addition, the teaching materials displayed are quite interesting because the form of practice used is quite good and interesting so that they can practice speaking and expressing opinions using polite language.